Reply to "Comment on "Critical analysis of a variational method used to describe molecular electron transport"" - Bâldea, Ioan; Köppel, Horst (Physical review. B, Condensed matter and materials physics, 2011)
Delaney and Greer [DG incorrectly assert that in Phys. Rev. B 80, 165301 (2009)] (denoted as I) we have “generalized” a transport approach proposed by them. In reality, we have criticized and demonstrated the complete failure of that approach. The Comment is based on the false supposition that real orbitals are constrained in I. We show that the complex orbitals suggested by DG as a way-out solution merely represent a particular case of the general case considered in I, which do not in the least affect our conclusion. The scattering states mentioned in their abstract in a sentence that is not substantiated by the main text of the Comment pertain to the correct Landauer approach. They have nothing in common with the incorrect DG variational approach. In conjunction with the issues raised by DG, we show that, astonishingly, by uncritically imposing the Wigner constraints in their original work [Phys. Rev. Lett. 93, 036805 (2004)], DG actually constrained the outgoing and not incoming charge carriers, which makes absolutely no sense for transport.